Olanzapine and fluoxetine combination therapy for treatment-resistant depression: review of efficacy, safety, and study design issues - William V Bobo (Dove Medical Press, 2009)
William V Bobo, Richard C SheltonDepartment of Psychiatry, Vanderbilt University School of Medicine, Nashville, TN, USAAbstract: Treatment-resistant depression (TRD) is a common occurrence in clinical practice. Up to 30% of patients with major depression do not respond to conventional antidepressant treatment, while a significantly greater number of patients experience only partial symptom reduction. Numerous strategies may be applied by the practicing clinician to overcome limitations in the effectiveness of antidepressant monotherapy, including combining drug treatment with evidence-supported psychotherapies, combining antidepressants (combination pharmacotherapy), and combining antidepressants with other non-antidepressant psychotropic medications (augmentation treatment). One such augmentation strategy, the combination of the selective serotonin reuptake inhibitor, fluoxetine (FLX), with the atypical antipsychotic drug, olanzapine (OLZ), is supported by the results of four randomized, double-blind, acute phase studies of patients who had responded inadequately to antidepressant monotherapy. In each study, the FLX/OLZ combination caused rapid reduction in Montgomery-Asberg Depression Rating scale scores, with two of the four studies showing significantly greater improvement than antidepressant monotherapy at study endpoint. Effects of the FLX/OLZ combination were strongest in cases where failure to respond to two antidepressants prior to randomization was established during the current depressive episode. The FLX/OLZ combination was well-tolerated; however, body weight gain and increases in prolactin were greater than that of the antidepressant monotherapy groups, and were comparable to that of OLZ monotherapy. While effective during acute-phase treatment, questions remain regarding the long-term efficacy and safety of FLX/OLZ relative to antidepressant monotherapy and other combination strategies. Efforts aimed at determining the placement of FLX/OLZ among the available options for addressing TRD are limited by lack of comparison and sequential treatment studies. Important aspects of study design and directions for future research are discussed.Keywords: olanzapine, fluoxetine, combination therapy, major depression, treatment resistance